Higher Order Thinking Skills: Student Profile Using Two-Tier Multiple Choice Instrument - Andriyatno, Indri; Zulfiani, Zulfiani; Mardiati, Yuke (International Journal of STEM Education for Sustainability, 2023)
This research aimed to analyze students' Higher Order Thinking Skills (HOTS) using a two-tier multiple choice (TTMC) test instrument. This study used a descriptive quantitative method with a purposive sampling technique. The instruments used are multiple-choice tests with free reasoning, the TTMC test for quantitative data, interview guides, and learning observations for qualitative data. Anderson and Krathwohl's Bloom taxonomy revision (2001) cognitive instrument used to classify HOTS. The results showed that the higher-order thinking skill profile has an average score of 63,21 and dominated good. Students' cognitive level of analyzing/C4 (74,35%) is more dominant compared to cognitive evaluating/C5 (68,90%) and creating/C6 (63,24%). The hormonal regulatory subconcept gets the highest correct answer average with a percentage of 89,74%, and the contraceptive method subconcept gets the lowest correct answer average with 35,90%. One factor that influences the high and low percentage of the correct answer for each subconcept is the level of difficulty of the question; medium (enough) in the contraceptive method and too tricky in the contraceptive method. Analysis of answer patterns based on the results of a TTMC test shows that students are better able to answer questions on the first tier than answering on the second tier.